2004
DOI: 10.1152/physrev.00032.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Insulin Resistance

Abstract: Insulin resistance plays a key role in the pathogenesis of several human diseases, including diabetes, obesity, hypertension, and cardiovascular diseases. The predisposition to insulin resistance results from genetic and environmental factors. The search for gene variants that predispose to insulin resistance has been thwarted by its genetically heterogeneous pathogenesis. However, using techniques of targeted mutagenesis and transgenesis in rodents, investigators have developed mouse models to test critical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
157
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(180 citation statements)
references
References 263 publications
5
157
0
8
Order By: Relevance
“…Rather, they indicate that FGF21 improves hepatic insulin action indirectly by stimulating hepatic fatty acid disposal. Decreasing hepatic fatty acid content has well-documented effects on liver insulin sensitivity in a variety of models and indirectly improves the responsiveness of hepatic glucose production, via either glycogenolysis or gluconeogenesis (38,39). In this respect, the effects of FGF21 are analogous to those of PPAR␣ agonists, which improve hepatic insulin action and overall glycemic control in diabetic rodents despite increasing hepatic gluconeogenesis (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they indicate that FGF21 improves hepatic insulin action indirectly by stimulating hepatic fatty acid disposal. Decreasing hepatic fatty acid content has well-documented effects on liver insulin sensitivity in a variety of models and indirectly improves the responsiveness of hepatic glucose production, via either glycogenolysis or gluconeogenesis (38,39). In this respect, the effects of FGF21 are analogous to those of PPAR␣ agonists, which improve hepatic insulin action and overall glycemic control in diabetic rodents despite increasing hepatic gluconeogenesis (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 is also downregulated since day 12, suggesting that this protein may be involved in the malfunction of the classical insulin pathway that could result in insulin resistance [18].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of Irs2 -/-mice has revealed that IRS2 signals are required for proper development and function of pancreatic β-cells as well as for the central regulation of appetite (10,11). Indeed, beta cellspecific overexpression of IRS2 promotes beta cell growth, survival, and insulin secretion that prevents diabetes in Irs2 -/-, obese and streptozotocin-treated mice (12).…”
Section: Introductionmentioning
confidence: 99%